Malay Folk Literature in Early Childhood Education among Malaysians - Peng, Chew Fong; Ishak, Zahari (EDUCARE, 2009)
ABSTRACT: Malay folk literature in early childhood education served as an important agent in child development that involved emotional, thinking and language aspects. Up to this moment not much research has been carried out in Malaysia particularly in the teaching and learning aspects nor has there been an effort to publish âbig booksâ. Hence, this article will discuss the stance taken by university undergraduates, teachers and parents in evaluating Malay folk literature in early childhood education to be used as big books. The data collated and analyzed were taken from 941 respondents comprising 347 graduates, 299 teachers and 295 parents. Results of the study indicated that Malay folk literature can be absorbed into teaching and learning for early childhood with a mean of 4.12 while it can be big books with mean of 4.02. Meanwhile the highest mean value required for placing Malay folk literature genre as big books in early childhood education rests on exemplary stories and animal fables with mean values of 4.22 and 4.19 respectively. The lowest mean value of 3.45 is given to lipurlara stories. The one-way ANOVA analysis has been concluded and has revealed a significant relationship between the graduates, teachers and parents with all the items for the teaching and learning of Malay folk literature or the items for the contents of the big book in early childhood education.KEY WORDS:Â Malay folk literature, early childhood education, narrative and non-narrative stories, and big book in Malaysia.Â Â About the Authors: Dr. Chew Fong Peng and Zahari Ishak, M.A. are Lecturers at the Faculty of Education UM (University of Malaya) in Kuala Lumpur, Malaysia. They could be reched at: fpchew@um.edu.my and irahaz@um.edu.myHow to cite this article? Peng, Chew Fong & Zahari Ishak. (2009). âMalay Folk Literature in Early Childhood Education among Malaysiansâ in EDUCARE: International Journal for Educational Studies, Vol.2(1) August, pp.69-82. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 3, 2009); Revised (July 3, 2009); and Published (August 17, 2009).